2022
DOI: 10.3390/genes14010117
|View full text |Cite
|
Sign up to set email alerts
|

Satellitome Analysis on Talpa aquitania Genome and Inferences about the satDNAs Evolution on Some Talpidae

Abstract: In the genus Talpa a new species, named Talpa aquitania, has been recently described. Only cytogenetic data are available for the nuclear genome of this species. In this work, we characterize the satellitome of the T. aquitania genome that presents 16 different families, including telomeric sequences, and they represent 1.24% of the genome. The first satellite DNA family (TaquSat1-183) represents 0.558%, and six more abundant families, including TaquSat1-183, comprise 1.13%, while the remaining 11 sat-DNAs rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…According to the satelitome composition and patterns of chromosomal distribution of satDNAs, Amosova et al [ 123 ] confirmed that genomes of the grass Deschampsia sukatschewii and D. cespitosa were more closely related in comparison to D. antarctica . Similarly, satellitome analysis on Aquitanian mole Talpa aquitania and further extension on related species showed that most of the satDNA families are present in the genomes of the other Talpa species analyzed, while only some in the genomes of other more distant Talpidae [ 117 ]. Following that, comparative analysis of morabine grasshopper genomes revealed that 102 out of 129 satDNA families were shared among the four inspected chromosomal races of the species Vandiemenella viatica , and 50 of the shared satDNA families underwent differential proliferation since the recent diversification of the V. viatica species complex [ 121 ].…”
Section: Comparative Satellitome Analysis: Satellitome and The Librar...mentioning
confidence: 99%
“…According to the satelitome composition and patterns of chromosomal distribution of satDNAs, Amosova et al [ 123 ] confirmed that genomes of the grass Deschampsia sukatschewii and D. cespitosa were more closely related in comparison to D. antarctica . Similarly, satellitome analysis on Aquitanian mole Talpa aquitania and further extension on related species showed that most of the satDNA families are present in the genomes of the other Talpa species analyzed, while only some in the genomes of other more distant Talpidae [ 117 ]. Following that, comparative analysis of morabine grasshopper genomes revealed that 102 out of 129 satDNA families were shared among the four inspected chromosomal races of the species Vandiemenella viatica , and 50 of the shared satDNA families underwent differential proliferation since the recent diversification of the V. viatica species complex [ 121 ].…”
Section: Comparative Satellitome Analysis: Satellitome and The Librar...mentioning
confidence: 99%
“…They are frequently located in pericentromeric and terminal regions of the chromosomes. However, intercalary heterochromatin also exhibits occurrence of satDNAs (de Lima et al, 2020; García‐Souto et al, 2017; González et al, 2021; Gutiérrez et al, 2022). Additionally, some examples of satDNAs populating euchromatin have been reported, albeit in smaller quantities (Garrido‐Ramos, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has allowed the characterization of satDNAs in the genomes of numerous non‐model species from different groups. For example, satDNAs have been studied in insects (Anjos et al, 2023; Cabral‐de‐Mello et al, 2021; Mora et al, 2020; Pita et al, 2017), mollusks (Tunjić‐Cvitanić et al, 2021), fishes (Goes et al, 2022; Kretschmer et al, 2022), frogs (da Silva et al, 2020; da Silva et al, 2023), mammals (Gutiérrez et al, 2022) and plants (Heitkam et al, 2021; Sader et al, 2021). Consequently, low‐abundance satDNAs have been characterized, and some of them have been found in euchromatin (Cabral‐de‐Mello et al, 2021; Milani et al, 2021; Montiel et al, 2021; Pita et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The satellitome, which is made up of the whole collection of satellite DNAs (SatDNAs) in a genome, offers an excellent opportunity to elucidate the dynamics of such components in the formation and upkeep of heteromorphic sex chromosomes [ 26 , 27 ]. Recent data provided a significant source of information for characterizing the satellitome of a variety of organisms, from insects [ 28 , 29 , 30 , 31 , 32 ] to fishes [ 25 , 33 , 34 , 35 , 36 , 37 ] frogs [ 38 , 39 ], lizards [ 40 ], birds [ 41 ], and mammals [ 42 , 43 , 44 , 45 ]. In general, SatDNAs are typically found in the centromeric, telomeric, and heterochromatic regions [ 46 ].…”
Section: Introductionmentioning
confidence: 99%